(untitled) (Global Journal of Science Frontier Research, 2012)
Global warming, the gradual increase in Earth’s temperatures and associated changes in global weather pattern, has had serious consequences in recent decades, constituting one of the major global issues of our time. This review highlights the sources of global warming, the country origins of Green House Gases (GHGs) emissions, the nexus between global warming and human activity, the costs of climate change drawing on findings on agricultural activity and, finally, policies to tackle global warming. The consequences of global warming still remain a subject of debate and speculation, but climate change studies hypothesize dire consequences for agricultural productivity and disease incidence globally, but especially for countries located nearer the tropics where temperatures are bound to rise higher.